Dynamics of bias instability in the tungsten-indium-zinc oxide thin film transistor. Issue 4 (9th January 2019) - Park, Hyun-Woo; Kwon, Sera; Song, Aeran; Choi, Dukhyun; Chung, Kwun-Bum
Abstract : The key to full understanding of the degradation mechanism of oxide thin film transistors (Ox-TFTs) by gate bias stress is to investigate dynamical changes of the electron trap site at the channel region while a real-time gate bias is applied to the actual thin film transistor (TFT) structure. Abstract : The key to full understanding of the degradation mechanism of oxide thin film transistors (Ox-TFTs) by gate bias stress is to investigate dynamical changes in the electron trap site in the channel region while real-time gate bias is applied to the actual thin film transistor (TFT) structure. In this study, we first investigated the dynamical changes in an electronic structure, such as the unoccupied states in the conduction band, and the band edge states below the conduction band of the active channel layer in the actual TFT structure under real-time gate bias. The dominant mechanism responsible for the degraded device stability of WIZO-TFTs by gate bias stress is a strongly correlated change in the unoccupied states in the conduction band and the band edge states below the conduction band by real-time gate bias.